Phrasems with Component ‘Ass’ in German and in Indonesian Language - Ajie, Raden Muhammad Arie Andhiko (Nusantara Science and Technology Proceedings)
This research is a contrastive comparison between German and Indonesian phrasems with the component "Arsch" (ass). In order to limit the analysis, only German phrasems, more precisely somatisms, with the component "Arsch" are compared with the Indonesian phrasems. This component is deliberately chosen to answer the following questions: 1. Are there suitable equivalents in Indonesian for the German phrasems with the component “Arsch”? 2. If not, what steps can be taken to find the equivalents? 3. What are the potential problems of finding the equivalents? Duden 11 (Dictionary of German Idiomatics) is used as the basis for this qualitative analysis. To search for equivalents in Indonesian, Kamus Besar Bahasa Indonesia online version, Kamus Ungkapan Bahasa Indonesia by Badudu (2009) Kamus Peribahasa by Badudu (2009) and Kamus Ungkapan Bahasa Indonesia by Mahayana et al. (1997) are used. Search engines such as Google and the online news portal www.tribunnews.com are consulted during the search so that the equivalents are corpus-validated. It turns out that there are only six phrasems in Indonesian that contain the word “pantat” (ass). The six phrasems consist of an idiom and five proverbs. There is no full equivalence. Thorough dictionary research is required to find equivalents. In order to check whether the equivalents are in use, an internet research should be carried out. Problems with finding equivalents have arisen because of the scarcity of Indonesian phraseological dictionaries. Another challenge is the lack of stylistic information and the problem with the currency of the registered phrasems.